Thermal, Infrared and X-Ray Diffraction Studies on Manganese and Zinc Soaps - Upadhyaya, S.K.; S. Sharma, Prem (Asian Journal of Chemistry, 2010)
The IR results showed that manganese and zinc laurates and palmitates have an ionic character. The X-ray diffraction patterns indicated that the zig-zag chains of fatty acid radical constituent of the soap molecules extend straight forward on both sides of each basal plane and the molecular axes of the soap molecules are somewhat inclined to the basal plane and these soaps possessed single layer structure. The thermal decomposition of manganese and zinc soaps has been studied both as a function of temperature and of time. The thermogravimetric analysis has shown that the order of decomposition reaction is kinetically of zero order and the energy of activation for the process lies in the range of 27-36 kJ mol–1.